Doing research in sound design - Filimowicz, Michael (Abingdon, Oxon New York Routledge, 2022)
oing Research in Sound Design' gathers chapters on the wide range of research methodologies used in sound design. Editor Michael Filimowicz and a diverse group of contributors provide an overview of cross-disciplinary inquiry into sound design that transcends discursive and practical divides. The book covers Qualitative, Quantitative and Mixed Methods inquiry. For those new to sound design research, each chapter covers specific research methods that can be utilized directly in order to begin to integrate the methodology into their practice. More experienced researchers will find the scope of topics comprehensive and rich in ideas for new lines of inquiry. Students and teachers in sound design graduate programs, industry-based R&D experts, and audio professionals will find the volume to be a useful guide in developing their skills of inquiry into sound design for any particular application area"--
Sound Design Thinking / Vincent Meelberg -- Meaning-making and Embodied Cognition in Sound Design Research / Stephen Roddy and Brian Bridges -- Mapping Space and Time in the Soundtrack: Embodied Cognition and the Soundtrack's Spatiotemporal Contract / Adam Melvin and Brian Bridges -- Measuring People's Cognitive and Emotional Response: Psychophysiological Methods to Study Sound Design / Emma Rodero -- Watching and Evaluating Simultaneously : an Approach to Measure the Expressive Power of Sound Design in a Moving Picture / Maximilian Kock -- Qualitative Research Methods for Sound Design Research / Dylan Davis -- Using a Semiotic Approach to the Practice of Sound Design / Leo Murray -- Audi(o) Branding and Object Sounds in an Audio-visual Setting : the Case of the Car / Nicolai Jørgensgaard Graakjær -- Designing and Reporting Research on Sound Design and Music for Health : Methods and Frameworks for Impact / Kjetil Falkenberg Hansen and Emma Frid -- Practice-led and Interdisciplinary Research : Investigating Affective Sound Design / Stuart Cunningham and Jon Weinel -- Research-creation as a Generative Approach to Sound Design / Prophecy Sun, Kate Hennessey, Kristin Carlson -- The Soundscape Approach : New Opportunities in Sound Design Practice / Ian Thompson -- Developing a Sound Design Creative A.I. Methodology / Miles Thorogood -- Sonification Research : Overview and Emerging Topics / Sandra Pauletto, Roberto Bresin -- Sound Design in the Context of Sonification / Visda Goudarzi -- Creating and Evaluating Aesthetics in Sonification / Nuria Bonet Filella -- Revealing Industry Culture : a Cultural Ethnographic Approach to Post-production Sound / Vanessa Ament -- Sound Design as Viewed by Sound Designers : a Questionnaire About People, Practice, and Definitions / Laura Zattra, Nicolas Donin, David Fierro, Frank Pecquet, and Nicolis Misdarlis -- Qualitative, Pragmatic, and Hermeneutic Inquiries in Electroacoustic Compositions : Selected Case Studies / Maria Kallionpää -- The Bold and the Beautiful Methods of Sound Experience Research : An Introduction to Mixing the Qualitative and Quantitative Study of the Subjective Experience of Sound and Music in Video Games / Hans-Peter Gasselseder.
includes bibliographical references and index.
cription based on print version record and CIP data provided by publisher.
Keywords: nd design -- Research